1968
DOI: 10.1080/00288306.1968.10423673
|View full text |Cite
|
Sign up to set email alerts
|

The Magnetotelluric method for locating major geological features and its application in the Wairarapa

Abstract: In the magnetotelluric analysis proposed by Cagniard, a resistivity profile of a homogeneous stratified earth is determined from the ratio of the tangential components of the natural electric and magnetic field fluctuations at the surface of the Earth. Two methods of this analysis are discussed and applied to measurements made in the W airarapa. One method gives a conducting surface layer of 4 km followed by a highly resistive substratum; the other gives a discontinuity at 14 km.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1985
1985
1985
1985

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Both the resistivity and thickness of the uppermost layer at REI are significantly greater than at either KAI or GaL. The resistivity structures for KAI and GaL are essentially consistent, both with each other and with the structure obtained by Christoffel & Linford (1968) for a site near Martinborough slightly south of the line of the sites in this study. A surface layer of low resistivity is underlain by a much more resistive layer.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Both the resistivity and thickness of the uppermost layer at REI are significantly greater than at either KAI or GaL. The resistivity structures for KAI and GaL are essentially consistent, both with each other and with the structure obtained by Christoffel & Linford (1968) for a site near Martinborough slightly south of the line of the sites in this study. A surface layer of low resistivity is underlain by a much more resistive layer.…”
Section: Discussionsupporting
confidence: 85%
“…Comparatively few such investigations have, however, been carried out in New Zealand. The major exception is the work of Midha (1979), and smaller studies have been reported by Christoffel & Linford (1968) and Hurst (1974).…”
Section: Introductionmentioning
confidence: 99%